PREVALENCE AND ASSOCIATED RISK FACTORS OF REPEAT BREEDING SYNDROME IN CATTLE HERDS OF SOUTHERN ADAMAWA STATE, NIGERIA - Solomsi, A. A.; Bobbo, A. G.; Sorau, S. M.; Abdulkadir, M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was conducted to determine the prevalence and identify risk factors associated with repeat breeding syndrome (RBS) in cattle herds in southern Adamawa State, Nigeria. A cross-sectional study was conducted across three Local Government Areas (Ganye, Jada, and Toungo), involving 60 randomly selected herds and 1,842 cattle. Data were collected using structured questionnaires, clinical examinations, and farm records. A cow was defined as a repeat breeder if it had failed to conceive after at least three services. The overall prevalence of RBS was 10.48% (193/1842). The prevalence varied significantly (p<0.05) across LGAs, with Ganye having the highest (4.56%), followed by Jada (3.42%) and Toungo (2.50%). Breed was a significant risk factor, with Crossbreeds 12.21% and White Fulani (11.13%) showing higher susceptibility than Adamawa Gudali (8.34%). Management system greatly influenced prevalence, with extensive systems having the highest rate (12.77%), compared to semi-intensive (8.43%) and intensive systems (7.58%). Parity and age were also significant factors; first-parity cows (12.31%) and cows over 8 years old (26.23%) had the highest prevalence. The study concludes that RBS is a prevalent condition in the study area, significantly influenced by location, breed, management system, parity, and age. Promoting semi-intensive and intensive management, strategic culling of older cows, and breed-specific reproductive management strategies were recommended.